Highly GC-rich heterochromatin in chili peppers (Capsicum-Solanaceae): A cytogenetic and molecular characterization - Grabiele, Mauro; Debat, Humberto Julio; Scaldaferro, Marisel Analía; Aguilera, Patricia Mabel; Moscone, Eduardo Alberto; Seijo, José Guillermo; Ducasse, Daniel Adrian (Elsevier, 2018)
Capsicum comprises 35 species of chili peppers and five of them are cultivated worldwide as spices or vegetables. Diploid karyotypes based in x = 12 and x = 13 are common in Capsicum and the constitutive heterochromatin (cHet) is of particular interest in the genus since it is largely variable, particularly its highly GC-rich fraction. However, the repetitive DNA components of this heterochromatic regions are unknown. Given the co-localization of rDNA loci with the CMA+DAPI– heterochromatic bands, we tested the hypothesis that the highly GC-rich cHet fraction is composed of the whole 18S-25S ribosomal DNA (rDNA) unit or some of its components. Here we report on a novel satellite for Capsicum and Solanaceae composed of the complete rDNA unit. We physically mapped six Capsicum derived specific 18S-25S rDNA probes that covered the entire span of the rDNA unit and analysed a DraI restriction product on eight chromosomally different taxa of Capsicum, representative of the major phylogenetic clades of chili peppers. The co-localization of every gene and spacer probes of the 18S-25S rDNA unit suggest their structural function as a major repetitive component of the highly GC-rich cHet in Capsicum species with x = 12. In addition, analyses of the clones derived from restriction assays in C. pubescens suggested that the differential functional status of 18S-25S rDNA loci (nucleolar organizer regions -NORs- or cHet) in this species is related to a divergence in a short sequence upstream the regulatory transcription initiation site (TIS) of the intergenic spacer (IGS). The results here provided evidence that an rDNA mega satellite played a significant role in the evolution of the karyotype features of x = 12 Capsicum species. The finding of a mega satellite family derived from the whole rDNA unit is a novelty for plant genomes